Identification of an amino acid metabolism-associated gene signature predicting the prognosis and immune therapy response of clear cell renal cell carcinoma - Zhang, Fan; Lin, Junyu; Zhu, Daiwen; Tang, Yongquan; Lu, Yiping; Liu, Zhihong; Wang, Xianding (Frontiers in Oncology, 2022)
Background: Upregulation of the amino acid metabolism is an essential form of metabolic reprogramming in cancers. Here we developed an amino acid metabolic signature to predict the prognosis and anti-PD-1 therapy response in clear cell renal cell carcinoma (ccRCC). Methods: According to amino acid metabolism-associated gene sets contained from the Molecular Signature Database, consensus clustering was administered to identify patients into two clusters. An amino acid metabolism-associated signature was further cultivated and verified. Immune cell infiltrates and the corresponding signature risk scores were investigated. Two independent cohorts of clinical trials were analyzed to explore correspondence of the signature risk score with immune therapy response. Results: Two clusters with different amino acid metabolic level were identified by consensus clustering. The patients in two clusters were different in overall survival, progression-free survival, amino acid metabolic status and tumor microenvironment. We identified a signature containing eight amino acid metabolism-associated genes which can accurately predict the prognosis of ccRCC patients. Signature risk score was positively correlated with infiltration of M1 macrophage, T cell CD8+, and regulatory T cells, whereas negatively correlated with neutrophil, NK cell, and CD4+ T cells. Patients with lower risk scores have better overall survival but worse response to nivolumab. Conclusion: Amino acid metabolic status has a close correlation with the tumor microenvironment, the response to checkpoint blockade therapy, and the prognosis in patients with ccRCC. The established amino acid metabolism associated gene signature can predict both the survival and anti-PD-1 therapy response of the patients with ccRCC.